Impact of Digitalization, Economic Growth and Birth Rate on Female Labor Force: Evidence from Kazakhstan - Kakizhanova Tolkyn; Utepkaliyeva Kansulu; Zeinolla Saule; Aben Assel; Ilyashova Guliya (ECONOMICS)
The purpose of the research work is to determine impact of the economic growth, digitization indicators and birth rate on female labor force in the Kazakhstan. For this purpose, Autoregressive Distributed Lag (ARDL) method was used. Data were obtained from the WDI website for period 1994–2022. Individuals using internet, Mobile cellular subscriptions (MCS), ICT service exports were taken as indicators of digitalization, and GDP growth was taken as indicator of economic growth. As a result of ARDL model, Internet users are negatively linked to the female labor force both in the short and in the long term. Mobile cellular subscriptions have a positive influence on the female labor force only in the short term, and however, showed its insignificance in the long term. ICT service export and GDP growth has a positive effect on the female labor force both in the short term and in the long term. Fertility rate has a positive effect on female labor force in the short and long term. Research work includes review of world literature and, based on this, an econometric model for Kazakhstan was created, and further presents proposals on how women’s employment can increase economic growth in Kazakhstan, also a comprehensive literature review and updated econometric model were developed. This research work carried can be used by other researchers for their regions of interest, and further recommendations can be considered in their case study.